L1-Educational Studies in Language and Literature - Rijlaarsdam, Gert.; Kooy, Mary.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: .)
As of 2006 this journal is no longer published by Springer. For later issues see L1 Educational Studies in Language and Literature (link: http://www.l1research.org/).
Keywords: Psycholinguistics; Language and education; Language Education; Psycholinguistics